MAXILLARY FIRST MOLAR DISTALIZATION WITH THE FROG APPLIANCE A CASE REPORT - Eduard Radu Cernei; Laura Gavrila; Dana Cristiana Maxim; Veronica Pintiliuc-Serban; Irina Nicoleta Zetu (Romanian Society of Oral Rehabilitation, 2015)
Traditional upper molar distalization techniques require patient co-operation with the headgear or elastics. Recently, several different intraoral procedures have been introduced to minimize the need for patient cooperation. Distalizing maxillary first molars is often an objectiv in treatment plans inolving Class II malocclusions and is sometimes indicate for non-extraction treatments with maxillary crowding. Pacient compliance has become a factor in choosing effective orthodontic appliances. In recent years various appliances that do not require patient compliance have been developed to drive maxillary molars distally. Some of these appliances produce unwanted tipping of the maxillary molars and a tendency to create crossbites if not properly adjusted. Therefore we want to present a case that presented in the clinic of Orthodontics and dento-facial orthopedics in the Ambulatory Pediatric Dentistry in Iasi. L.S. patient aged 12 years presenting for aesthetic and functional disorders. On examination extraoral facial changes occur hyperdivergent profile. Clinical examination reveals intraoral Angle Class I molar malocclusion, anterior deep bite, mesial inclination of the lower left permanent molar. Upper canines teeth are erupting bucally, due to lack of space. OPT examination and anamnesis reveled reduction the space for the lower left second premolar and for the lower right canin probabily due to premature loss of second primary molar and primary canine. Indicate a slight lateral cephalometric skeletal Class II (∠ ANB inv. = 5.040) with a hyperdivergent profile ∠GoGn/SN=360 .We wanted a non extraction treatment except the 3rd molars.. The treatment plan included distalization of the upper first molars bilaterally followed by a palatal expander and a full fixed appliance therapy. For the lower arch we applied a lip-bumper for moderate arch expansion and for lower molars distalization. For the upper molar distalization, a new system, the Frog Appliance, was constructed and applied. Lateral cephalometric radiographs were used to evaluate the treatment results. It was obtained an over distalization of the first molars after 10 mouths of treament because the patient missed the subsequent checks. The lower lip-bumper was not carried. According to the results of the cephalometric evaluation, a nearly bodily distal molar movement was attained. It was reapplied lip bumper and a palatal expander. The patient is still in treatment. In conclusion, the Frog Appliance was found to be effective, non-invasiv appliance for achieving bilateral molar distalization, but the patients should be more motivated to come to check up.